Food Security in Nepal: A Review - Chemjong, Badal; KC, Yadav (Rupantaran: A Multidisciplinary Journal, 2020)
Nepal has improved food security situation in recent years, but still considered as a poor country in the world. The main objective of this paper is to evaluate the food security situation in Nepal. Food insecurity in Nepal has been associated with susceptibility to natural disasters, such as drought, governance, earthquake, floods, and landslides, vulnerability to fluctuations in global prices, civil turmoil, disease and poor infrastructures. Pandemic COVID-19 is degrading the daily life of the people and driving to food insecurity in the country. Mostly western Nepal and Terai region seems to be more vulnerable to disasters and food insecurity. In Nepal, 4.6 million people are food-insecure, with 20 percent of household mildly food-insecure, 22 percent moderately food-insecure and 10 percent severely food-insecure. This problem needs to be solved by a clear and sound policies and strategy by putting natural resources conservation in consideration.